WHO orchestrates? - Tine Hanrieder (International Organizations as Orchestrators, 2015)
This chapter examines how the WHO's orchestrating role has been reshaped by the proliferation of actors in the international health field. Lacking the material capabilities to perform its technical functions on its own, WHO traditionally draws on its formal authority and convening power to mobilize other international organizations and non-governmental associations for research, surveillance and technical assistance activities. Yet as this chapter demonstrates, the growing density of the health field since the 1980s has played out differently on WHO's ability to orchestrate. Comparing the domains of epidemiological surveillance and technical assistance, I argue that IGO focality is critical for recruiting new actors as intermediaries. As WHO's recent empowerment in health surveillance demonstrates, new intermediaries can become powerful allies that allow a focal IGO to engage in orchestration, and even to gain greater autonomy from member-state oversight. By contrast, as WHO lacks focality in the developmental domain, its attempts to orchestrate health assistance are increasingly frustrated. Additionally, states have used new exit options to strengthen their oversight over WHO through project-specific contracts. Thus, this within-case comparison not only illuminates the inter-organizational dynamics underlying orchestration, but also points out how focality, intermediary availability and state oversight interact to either reinforce or undermine IGO orchestration.
Keywords: 300